« But in that room, in that presence, I was invertebrate » : la peur de l’autre dans The Beetle de Richard Marsh - Catherine Lanone (Cahiers Victoriens et Edouardiens)
Published in 1897, The Beetle by Richard Marsh was a great fin-de-siècle success which once rivalled the now arch-famous Dracula. Although it has almost sunk into oblivion, The Beetle may have been deemed powerful in its time because it displays all the archetypal fears haunting the nineteen-nineties, from degeneracy to mesmerism, reverse colonialism or the New Woman. It creates scenes of utmost terror which are extremely effective, however badly written the novel may be in parts. Exploring unstable areas, The Beetle is a striking example of suburban Gothic, pitting the supernatural creature against the vagrant, the lady, the politician or the scientist, in order to challenge social but also gendered boundaries.